Student Learning Outcomes and Motivation on Arts and Skills Education Course in PGSD Study Program of STKIP Taman Siswa Bima - Ifniati, Nur; Mulyanto; Sumartono, Basuki (Jurnal Multidisiplin Madani, 2024)
The objective of this study is to propose a case study method application which can improve student learning outcomes and motivation in the arts and skills education course in the PGSD study program at STKIP Taman Siswa Bima. This Classroom Action Research (CAR) study adopted the Kemmis and McTaggart's model design, which involves planning, implementation and evaluation.  The data were derived from primary data on learning outcomes and learning motivation after applying the case study learning method. The study object was to apply the case study learning method. The data collection methods include library studies, observation, tests, questionnaires, interviews, and documentation. The data analysis technically used a qualitative descriptive method. The study results revealed that the case study method is used in the PGSD study program at STKIP Taman Siswa Bima through conveying objectives and motivation, dividing students in groups, distinguishing cases, students having discussions, students delivering presentations, and evaluating learning. The case study method includes components of the Semester Learning Plan, media, materials, and learning objectives. The case study method can improve learning outcomes and student motivation in the arts and skills education course in the PGSD study program at STKIP Taman Siswa Bima. This can be measured by the increase in learning outcomes in Cycle III, where the completeness score was 100% and learning motivation was 96.7%